The Stakeholder Participation-Based Competency Empowerment Model of Creative Tourism Planning and Management in Phra Nakhon Si Ayutthaya World Heritage Site - Choibamroong, Therdchai; Lee-Anant, Chayapoj (Journal of Roi Kaensarn Academi, 2024)
Phra Nakhon Si Ayutthaya, once the flourishing capital of Thailand, was declared a UNESCO World Heritage site in 1991. Recently, the site has seen a significant influx of visitors, propelled by the success of Thai dramas like Love Destiny Seasons 1 and 2. This popularity has intensified the challenge of managing over-tourism effectively. Addressing these challenges necessitates comprehensive planning and strategic management, including intensive training programs designed to boost the competencies, skills, and knowledge of those involved in tourism planning and management. These efforts aim not only to enhance the area’s productivity but also its overall well-being. This study was driven by two primary objectives: 1) to identify and analyze the challenges and obstacles that have previously hindered effective tourism planning and management at the Ayutthaya World Heritage Site, with a particular emphasis on improving creative tourism management; and 2) to enhance the competencies, skills, and knowledge of tourism stakeholders through a creative tourism approach. Employing a mixed-methods strategy, the research involved two groups of 60 participants from six key informant categories, including representatives from central and local governments, the private sector, community sectors, civil society, and academia within Phra Nakhon Si Ayutthaya. The research tools utilized included semi-structured interviews, pre- and post-training assessments, and satisfaction surveys. The investigation uncovered 20 sub-themes, pinpointing the incompetence of manpower and personnel, budget constraints, and ineffective space utilization as the most pressing issues. These challenges have consistently impeded effective tourism management at the site. In response, a three-day intensive training program was developed and executed, significantly bolstering the necessary competencies, skills, and knowledge. The training’s impact was profound, with 93% of participants passing the post-training assessment and the majority expressing excellent overall satisfaction. Ultimately, this research lays out a replicable model for developing creative tourism planning and management competencies among tourism stakeholders. This model, adaptable to other locales with similar tourism resources, not only addresses immediate management needs but also establishes a framework for the sustainable development of heritage sites.